Beyond rational behaviour: the non-financial variables that condition shareholder action during a takeover. Issue 3 (3rd July 2017) - Mayoral, Rosa M.; Vallelado, Eleuterio
Abstract : This article provides experimental evidence that bidder and target shareholders of a takeover announcement exhibit differences in their actions explained by individual traits and by the environment in which investors must decide. These variables should be considered when designing an adequate investor protection policy. Before the crisis, investor protection regulation was based on the rational behaviour hypothesis and characterized by an overreliance on disclosure and financial literacy strategies. However, the new European policy on financial services has acknowledged the lack of adequate protection, and has increased transparency and access to information for investors in MIFID II and MiFIR.